Age and growth of the tilapia, Oreochromis niloticus (Perciformes: Cichlidae) from a tropical shallow lake in Mexico - Luis Gómez Márquez, josé (2008)
Age and growth of Nile tilapia (Oreochromis niloticus) were determined using 1 039 specimens collected in a tropical shallow lake of Mexico, from January to December 1993. Standard length of females ranged from 9.0 to 16.5 cm and males from 8.9 to 14.8 cm. The standard length?weight relationships for all individuals was BW=0.1207 SL2.469. The age data, derived from opercular bone readings, were used to estimate the growth parameters of the von Bertalanffy equation: L8=17.88 cm, K=0.3409, to=-1.543, and W8=149.21 g. The oldest male and female were 2.5 years old. The sex ratio (female:male) was of 1:1 (χ²=0.02, p > 0.05).